A Study of Prevalence of Hypertension among Urban and Rural Population and the Factors Associated with Hypertension - Ravi R Marinayakanakoppalu; Ashok C Nagaralu (Medsci Publications, 2017)
Introduction: Hypertension is increasing rapidly in most low and middle income countries. The actual burden of Hypertension in urban and rural India is often under estimated. There is a felt need to define actual burden of the disease and to determine the geographic differences in the prevalence of hypertension and the risk factors associated. Methodology: The present study was a across-sectional study conducted in Mysore district. Study included a total of 793 subjects. Individuals greater than 30 years of age were included. Data regarding basic demographic characteristics were collected along with anthropometric measurements including height and weight. Results: Prevalence of hypertension was 31.4% and 25.0% from urban and rural area respectively & was statistically significant (p=0.04). Factors such as salt intake, tobacco consumption, alcohol consumption, stress had a significant association (P < 0.05). Conclusion: The prevalence of hypertension was high in urban area (31.4%). Though prevalence of hypertension in rural area is low when compared to urban, it can be observed that it is increasing over time to match the urban rate. Present study emphasizes the fact that various risk factors are associated with the prevalence of hypertension.